History of Medical Informatics: From Punched Cards to Computerized Patient Records: A Personal Journey - Peterson, Hans E. (Yearbook of Medical Informatics, 2006)
This paper presents the early history of the development of CPR in Sweden, the importance of international cooperation and standardisation and how this cooperation has been facilitated by IMIA, the European Union and the standards organisations. It ends with the lessons learned after 35 years of experience put together by the Swedish Institute for Health Services Development, SPRI, in a 5 year project initiated by the Swedish Government and with participation of most health care providers in the country.Starting with the first attempts to use punched cards to store and use patient information for clinical use the author describes his troublesome and difficult road to a Computerized Patient Record that could be used both for the work with the patient and as a tool to follow up both the diagnostic and therapeutic processes and for clinical research.The most important results of the efforts to develop a computerized patient record in Sweden are published in many reports, among them three SPRI reports published in the late 1990s, and they are: Standardized information architecture, a common terminology, rules for communication, security and safety, electronic addresses to all units and users and an agreed upon patient and user identification.The future CPR must be problem oriented, capable of only adding new information instead of repeating already-known data and be available in real time regardless of geographic location. It must be possible to present the information in the CPR as “views” where the healthcare provider has stated in advance the information needed for his patients. There can be a number of “views” for different occasions.
Keywords: History of medical informatics; history of CPR; history of IMIA; international cooperation in health informatics